And then there were four ...: How many (and which) measures of active labor market policy do we still need? - Werner Eichhorst; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Through the Hartz reforms, German active labor market policy was fundamentally restructured and has since been systematically evaluated. This paper reviews the recent evaluation findings and draws some conclusions for the future setup of active labor market policies in Germany. It argues in favor of a reduced range of active labor market policy schemes focusing on programs with proven positive effects (that are wage subsidies, training, start-up grants and placement vouchers) and calls for a systematic evaluation of all instruments not scrutinized so far.
Keywords: D61; H43; J68; 330; active labor market policy; Germany; evaluation